2017
DOI: 10.1371/journal.pone.0190083
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a N4-like lytic bacteriophage infecting Vibrio splendidus, a pathogen of fish and bivalves

Abstract: A novel virulent bacteriophage, vB_VspP_pVa5, infecting a strain of Vibrio splendidus was isolated from a sea-cage aquaculture farm in Greece, and characterized using microbiological methods and genomic analysis. Bacteriophage vB_VspP_pVa5 is a N4-like podovirus with an icosahedral head measuring 85 nm in length and a short non-contractile tail. The phage had a narrow host range infecting only the bacterial host, a latent period of 30 min and a burst size of 24 virions per infected bacterium. Its genome size w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 67 publications
1
27
1
1
Order By: Relevance
“…The G7-like phages The E. coli phage N4, the prototype species of the group of N4-related viruses was a database orphan for many years (Kazmierczak et al 2002). However, over the last decade, numerous N4-like viruses that infect Gram-negative bacteria were isolated and sequenced (Faidiuk et al 2017;Golomidova et al 2007;Cai et al 2015;Patel et al 2015;Li et al 2016;Ma et al 2016;Shigehisa et al 2016;Bhattacharjee et al 2017;Katharios et al 2017;Buttimer et al 2018), and for reviews see (Chan et al 2014;Wittmann et al 2015). The N4-related sequences are also ubiquitous in human fecal metagenomes and viromes (Waller et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The G7-like phages The E. coli phage N4, the prototype species of the group of N4-related viruses was a database orphan for many years (Kazmierczak et al 2002). However, over the last decade, numerous N4-like viruses that infect Gram-negative bacteria were isolated and sequenced (Faidiuk et al 2017;Golomidova et al 2007;Cai et al 2015;Patel et al 2015;Li et al 2016;Ma et al 2016;Shigehisa et al 2016;Bhattacharjee et al 2017;Katharios et al 2017;Buttimer et al 2018), and for reviews see (Chan et al 2014;Wittmann et al 2015). The N4-related sequences are also ubiquitous in human fecal metagenomes and viromes (Waller et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggested that phages can be found in virtually all places where their related hosts exist. Several other investigations reported the presence of Vibrio-specific lytic phages in environmental water (shrimp ponds, aquaculture system, sea water and aquatic product market) from different regions of the world (Alagappan et al, 2010;Luo et al, 2016;Stalin and Srinivasan, 2016;Katharios et al, 2017;Srinivasan and Ramasamy, 2017;Yang M. et al, 2019).…”
Section: Origin and Morphology Of Phages Ba3 And Ca8mentioning
confidence: 99%
“…This study also elucidates that the phage is able to hijack protein translation machinery of the host bacteria. In comparison to other phages that infect vibrios (Table S2) [46][47][48][49][50][51][52] , phage Seahorse has relatively big burst size with a shorter latency period than phages VP-1, VP-2, VP-3, VpKK5, and VhKM4 that replicate in V. parahaemolyticus 27,29,[53][54][55][56] . It is also tolerant to the wide range of pHs and temperatures compared to other vibriophages suggesting unique survivability in harsh natural environments.…”
Section: Discussionmentioning
confidence: 96%
“…For pH stability, 100 μl of phage lysate was mixed with 900 μl of SM buffer in a pH range 2 to 10 and incubated at 30 °C for 1 hour. For temperature stability, 50 μl of phage lysate was incubated for 1 hour at different temperatures; 4,20,25,30,37,40,50,60, and 70 °C. For both tests, phage infectivity was determined by performing a spot test.…”
Section: Methodsmentioning
confidence: 99%